2011
DOI: 10.1259/bjr/56324742
|View full text |Cite
|
Sign up to set email alerts
|

The value of dual-time-point18F-FDG PET/CT for identifying axillary lymph node metastasis in breast cancer patients

Abstract: Objective: The sensitivity of 18-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) for detecting axillary lymph node (ALN) metastases in breast cancer is reported to be low. Several studies have shown, however, that dual-time-point 18 F-FDG PET imaging provides improved accuracy in the diagnosis of certain primary tumours when compared with single-scan imaging. The purpose of this study was to assess whether the use of dual-time-point 18 F-FDG PET/CT scans could improve the diagnostic accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…24,54,55 Several studies have investigated the applicability of DTPI for improvement of the results from FDG-PET/CT for diagnosis, assessment of axillary lymph nodes, and recurrence of breast cancer. 24,25,[56][57][58][59] Mavi and colleagues 24 in a study of 152 patients with DTPI observed an increase in the uptake of FDG at the second time point in patients with malignant breast lesions. They also noted differences in the increase of FDG uptake, which might reflect the tumor biology.…”
Section: Breastmentioning
confidence: 97%
“…24,54,55 Several studies have investigated the applicability of DTPI for improvement of the results from FDG-PET/CT for diagnosis, assessment of axillary lymph nodes, and recurrence of breast cancer. 24,25,[56][57][58][59] Mavi and colleagues 24 in a study of 152 patients with DTPI observed an increase in the uptake of FDG at the second time point in patients with malignant breast lesions. They also noted differences in the increase of FDG uptake, which might reflect the tumor biology.…”
Section: Breastmentioning
confidence: 97%
“…56 The study included 171 patients who underwent preoperative DP FDG-PET/CT (1 and 3 hours after radiotracer injection). Where FDG uptake in the axilla was perceptibly increased, the SUVs for both time points and the RI were calculated.…”
Section: Breast Cancermentioning
confidence: 99%
“…In a third study on 26 esophageal cancer patients specificity to detect metastatic lesions was improved when retention index (RI) 10% was used to supplement the early SUVmax of ≥ 2.5 (32) . On the other hand there are other studies that reported no improvement in diagnostic accuracy by the use of delayed imaging (33)(34)(35)(36) . In most of these studies the delayed SUVmax or RI were used separately versus the early SUVmax and not in conjunction with the early SUVmax.…”
Section: Discussionmentioning
confidence: 95%